Machining Temperature, Surface Integrity and Burr Size Investigation During Coolant-Free Hole Milling in Ti6Al4V Titanium Alloy - Shanmugam, Ragavanantham; Baloor, Satish Shenoy; Koklu, Ugur; Polishetty, Ashwin; Bolar, Gururaj (MDPI AG, 2023)
Modern Aircraft structures use titanium alloys where the processing of holes becomes essential to assemble aerospace parts. Considering the limitations of drilling, the study evaluates the helical milling for hole processing in Ti6Al4V. The experimental evaluation was conducted by considering burr size, surface roughness, machining temperature, and microhardness under coolant-free conditions. The axial feed and cutting speed were varied at three levels, and nine experiments were conducted. The results exhibit a lower machining temperature during helical milling than during drilling. In addition, the helical milling helped to lower the surface roughness and size of the exit burrs. However, helical-milled holes showed higher subsurface microhardness than conventionally drilled holes. The process variables were influential on machining temperature magnitude. The highest recorded temperature of 234.7 °C was observed at 60 m/min of cutting speed and 0.6 mm/rev feed. However, the temperature rise did not affect the microhardness. Strain hardening associated with mechanical deformation was the primary mechanism driving the increase in microhardness. Helical-milled holes exhibited an excellent surface finish at lower axial feeds, while chatter due to tool deformation at higher feeds (0.6 mm/rev) diminished the surface finish. The surface roughness increased by 98% when the cutting speed increased to 60 m/min from 20 m/min, while a moderate increment of 28% was observed when the axial feed increased to 0.6 mm/rev from 0.2 mm/rev. Furthermore, the formation of relatively smaller burrs was noted due to significantly lower thrust load and temperature produced during helical milling.
Keywords: 4012 Fluid mechanics and thermal engineering; 4017 Mechanical engineering